The THE INFLUENCE OF LIQUID ORGANIC FERTILIZER FROM COW MANURE ON THE GROWTH AND PRODUCTION OF LETTUCE (Lactuca sativa L.) Var Kriebo - Cicik Suriani; Serina Fitri Ayu Limbong; Fitri Afifah Nasution (Universitas Medan Area, 2023)
growth and production of lettuce plants. The study was conducted in an open field in Sampun Village, Dolat Rayat District, Karo Regency, North Sumatra Province. The research design was an experimental design a Non-Factorial Randomized Block Design with 4 treatments and 6 replications, making a total of 24 plant samples. The data were analyzed using Analysis of Variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT). The results showed that liquid organic fertilizer derived from cow manure had a significant effect on the growth and production of lettuce plants (Lactuca sativa L. var kriebo). The best plant growth was observed in treatment P3 (300 mL) with a plant height of 23 cm at 5 weeks after planting, 13 leaves, leaf area of 401.28 cm², and wet weight of 96 grams. The dosage that showed optimum results for the growth and production of lettuce plants was found in treatment P3 (300 mL).